417 Incidence and epidemiology of burns treated in the welsh centre for burns. (1st September 2016) - Walters, Angharad; Lyons, Ronan; Turner, Samantha; Fry, Richard; Potokar, Tom
Abstract : Background: It is important to understand the epidemiology of burns in order to support the development and refinement of preventative measures. We used population based data from the Welsh Centre for Burns and Plastic Surgery (catchment area 2.3 million people) to study trends in the epidemiology of burns. Methods: Anonymised data from the Welsh Burns Centre have been included in the Secure Anonymised Information Linkage (SAIL) databank and linked to a population register. To describe the epidemiology of burns treated at the centre, data were restricted to acute injury assessments/admissions between 01/01/2003 and 31/12/2012 for patients who lived in Wales. Results: During the 10 years, there were 7160 acute injury admissions/assessments. There is an increasing trend in the rates over the decade, increasing from 26.6 per 100, 000 population in 2003 to 31.9 in 2012. Rates of burns in the home have increased from 13.2 per 100 K in 2003 to 20.8 in 2012 and more specifically, rates of burns in the kitchen have increased. During 2012, rates of treated burns were highest in males aged 0–4. The 0–4 age group suffer mainly from scalds followed by contact burns; contact burn rates have doubled over the ten years for this group of patients. Over the decade, rates were highest in the most deprived quintiles; however the rates are increasing in the least deprived and a substantial narrowing of the inequality can be seen over time. The distance travelled to Morriston hospital does not appear to be increasing over time and the severity of the burns have not changed over the decade; therefore the increase in the rate of treated burns does not appear to be due to an increasing rate of transfers of more serious burns from other hospitals in Wales. Conclusions: Given increasing incidence and narrowing of inequalities more effective preventive interventions are needed.